Ambient temperature modulates the effects of the Prader-Willi syndrome candidate gene Snord116 on energy homeostasis. (February 2017) - Qi, Y.; Purtell, L.; Fu, M.; Sengmany, K.; Loh, K.; Zhang, L.; Zolotukhin, S.; Sainsbury, A.; Campbell, L.; Herzog, H.
Abstract: Germline deletion of the Prader-Willi syndrome (PWS) candidate gene Snord116 in mice leads to some classical symptoms of human PWS, notably reductions in body weight, linear growth and bone mass. However, Snord116 deficient mice ( Snord116 −/− ) do not develop an obese phenotype despite their increased food intake and the underlying mechanism for that is unknown. We tested the phenotypes of germline Snord116 −/− as well as neuropeptide Y (NPY) neuron specific Snord116 lox / lox / NPY cre /+ mice at 30 °C, the thermoneutral temperature of mice, and compared these to previous reports studies conducted at normal room temperature. Snord116 −/− mice at 30 °C still weighed less than wild type but had increased body weight gain. Importantly, food intake and energy expenditure were no longer different at 30 °C, and the reduced bone mass and nasal-anal length observed in Snord116 −/− mice at room temperature were also normalized. Mechanistically, the thermoneutral condition led to the correction of the mRNA expression of NPY and pro-opiomelanocortin (POMC), which were both previously observed to be significantly up-regulated at room temperature. Importantly, almost identical phenotypes and NPY/POMC mRNA expression alterations were also observed in Snord116 lox / lox / NPY cre /+ mice, which lack the Snord116 gene only in NPY neurons. These data illustrate that mild cold stress is a critical factor preventing the development of obesity in Snord116 −/− mice via the NPY system. Our study highlights that the function of Snord116 in the hypothalamus may be to enhance energy expenditure, likely via the NPY system, and also indicates that Snord116 function in mice is strongly dependent on environmental conditions such as cold exposure. Highlights: Snord116 plays a critical role in the development of Prader-Willi syndrome. Ambient temperature corrects the phenotypes caused by the deletion of Snord116 gene. Ambient temperature corrects the expression of neuropeptide Y and proopiomelanocortin. These alterations are via neuropeptide Y system.